Technique for the culture and direct sensitivity testing or large numbers of urine specimens. Issue 3 (March 1986) - Cheetham, P; Brown, S E
Abstract : A technique was required for batch culturing and direct sensitivity testing of urine specimens to reduce increasing demands on laboratory services. A comparison was made between the filter paper strip method and multipoint inoculator technique using a Denley inoculator (Denley Ltd, Billingshurst, Sussex). The results showed that multipoint inoculation was a rapid, economical, and reliable method for the handling of large numbers of urine samples.